Translating missio Dei Indispensable Bible translation in God’s mission - Thinane, Jonas Sello (2024)
Missio Dei , particularly from the 1952 International Missionary Council perspective, highlights God’s unmerited grace, which invites broad human participation in the realisation of salvation (Σωτηρία) and the kingdom of God (Βασιλεία τοῦ Θεοῦ). The achievement of these goals depends on divine providence and the involvement of churches, including but not limited to the vital ministry of Bible translation. The crucial role that Bible translation plays in mission is to overcome barriers that distinguish the nations of the world and to reconcile them towards the fulfilment of the purposes of missio Dei . Although Bible translation remains an indispensable component of mission, its critical importance has received little to no scholarly attention. Once Bible translation is no longer viewed through the lens of mission, it is likely to dissolve into mere translation activities that are incompatible with the missio Dei . There is, therefore, a need for research that uncovers this indispensable function in the overall work of the missio Dei and in the realisation of its goals. Based on available literature, this article highlights the importance of Bible translation in the context of the missio Dei . Complexity theory is used to accentuate the interactive nature of Bible translations in mission context. Further research is needed to develop a holistic framework that fully integrates Bible translation into the context of the missio Dei . Intradisciplinary and/or interdisciplinary implications: This article expands the interdisciplinary discourse between translation studies and theology by addressing the central importance of Bible translation work within missiology.
Keywords: Bible Translation; Missio Dei; mission of God; the Great Commission; total salvation